Design and two-photon direct laser writing of low-loss waveguides, tapers and S-bends. (24th August 2021) - Baghdasaryan, Tigran; Vanmol, Koen; Thienpont, Hugo; Berghmans, Francis; Geernaert, Thomas; Van Erps, Jürgen
Abstract: Despite the rapid developments in the field of two-photon polymerization-based direct laser writing, limited attention has been paid to the efficient design of optical waveguide-based building blocks. To fill that gap, we have numerically investigated air-clad waveguides, tapers, and S-bends, with the aim to minimize insertion losses, whilst reducing the device sizes. We have first demonstrated waveguides with square and circular cross-sections that are mode-matched with single-mode optical fibers featuring insertion losses below −0.6 dB and −1.5 dB around 1550 nm for lengths of respectively 0.2 mm and 1 mm. We have also identified parabolic tapers that allow for adiabatic transition between a wide range of input and output waveguide sizes. These shapes allow, for example, tapering down from 15 µ m to 2 µ m diameter waveguides over a length as short as 43.2 µ m. We have fabricated a series of such components and confirmed their nearly lossless performance with insertion loss measurements. Finally, we have designed and optimized S-bends with Bezier curve shapes. As a proof-of-principle demonstration, we have fabricated a 160 µ m long S-bend that offsets the waveguide axis by 50 µ m. The insertion loss of the resulting 400 µ m long component, which also included two parabolic tapers, was less than −1.7 dB. Apart from providing design rules and ready-to-use recipes for fabricating low-loss 3D-printed waveguide-based building blocks, we project that our work will spark the development of a series of efficient photonic devices that rely on these components and that can be exploited in diverse application fields.